Fast calculation of groundwater exfiltration salinity in a lowland catchment using a lumped celerity/velocity approach. (October 2017) - Delsman, Joost R.; de Louw, Perry G.B.; de Lange, Willem J.; Oude Essink, Gualbert H.P.
Abstract: To support operational water management of freshwater resources in coastal lowlands, a need exists for a rapid, well-identifiable model to simulate salinity dynamics of exfiltrating groundwater. This paper presents the lumped Rapid Saline Groundwater Exfiltration Model (RSGEM). RSGEM simulates groundwater exfiltration salinity dynamics as governed by the interplay between water velocity, gradually adjusting the subsurface salinity distribution, and pressure wave celerity, resulting in a fast flow path response to groundwater level changes. RSGEM was applied to a field site in the coastal region of the Netherlands, parameter estimation and uncertainty analysis were performed using generalized likelihood uncertainty estimation. The model showed good correspondence to measured groundwater levels, exfiltration rates and salinity response. Moreover, RSGEM results were very similar to a detailed, complex groundwater flow and transport model previously applied to this field site. Highlights: A novel, well-identifiable model to simulate salinity dynamics of exfiltrating groundwater. Conceptualizes water velocity and pressure wave celerity to simulate salinity dynamics. Results compare favorably to both measurements and a detailed groundwater model.